2004
DOI: 10.14310/horm.2002.11119
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with body mass index in adults from Northern Greece

Abstract: The aim of this large scale epidemiological cross-sectional study was to investigate potential factors, such as age, gender, socioeconomic status (measured as educational level and profession), smoking habits and physical activity, that could influence Body Mass Index (BMI) in a large sample of Greeks of Central Macedonia. Overall, 4032 adults (1296 males and 2736 females), age: 44.3+/-14.5 y (mean +/- SD) participated in this study. Candidates were contacted by phone and provided self-reported data about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
2
11
0
3
Order By: Relevance
“…Unfortunately, data on socioeconomic status are not available for our population. Two recent studies that evaluated factors associated with obesity prevalence in northern Greece and in the area of Attica found an inverse relationship between obesity prevalence and socioeconomic status [11,25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, data on socioeconomic status are not available for our population. Two recent studies that evaluated factors associated with obesity prevalence in northern Greece and in the area of Attica found an inverse relationship between obesity prevalence and socioeconomic status [11,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Obese men, on the contrary, experience less body dissatisfaction and less disordered eating. This probably relates to the patriarchal view of the body image in countries such as Greece, in which excess body weight, at least in lower classes, is still considered an indication of social status [25] . Some habits, such as smoking and alcohol consumption, could also play a role [28] .…”
Section: Discussionmentioning
confidence: 99%
“…17 In a European study, the EPIC-PANACEA survey, which was conducted in 9 European countries, it was demonstrated that both PA at work and leisure-time physical activity were inversely correlated with BMI and waist circumference. 11 Accordingly, most international studies found an inverse relationship between PA and OB.…”
Section: Discussionmentioning
confidence: 99%
“…Formülde birinci tercih 3 puan, ikinci tercih 2 puan ve üçüncü tercih ise 1 puan ile çarpılmış ve toplam puanlar elde edilmiştir. Yapılan çalışmalarda, üniversite öğrencilerinde beslenme alışkanlıkları çoğunlukla düzensiz olmakla beraber öğrencilerin beslenme profilleri düşük vitamin ve yüksek yağ alımı ile karakterizedir 12,13 .…”
Section: Yöntemlerunclassified